Protective and risk factors of workplace violence against nurses: A cross‐sectional study - Bagnasco, Annamaria; Catania, Gianluca; Pagnucci, Nicola; Alvaro, Rosaria; Cicolini, Giancarlo; Dal Molin, Alberto; Lancia, Loreto; Lusignani, Maura; Mecugni, Daniela; Motta, Paolo Carlo; Watson, Roger; Hayter, Mark; et al. (Journal of clinical nursing, 2024)
Aims To describe how workplace violence (WPV) is experienced by nurses in hospitals and community services and identify protective and risk factors. Methods An online cross‐sectional national study was conducted from January to April 2021 in Italy. Hospitals and community services were involved in the study. The survey combined the adapted and validated Italian version of the Violence in Emergency Nursing and Triage (VENT) questionnaire, which explores the episodes of WPV experienced during the previous 12 months, the Practice Environment Scale of the Nursing Work Index (PES‐NWI) and some additional questions about staffing levels extracted from a previous RN4CAST study. Nurses working in all clinical settings and community services were invited to participate in the survey. Descriptive and inferential statistics were used for data analysis. We adhered to the STROBE reporting guidelines. Results A total of 6079 nurses completed the survey, 32.4% (n = 1969) had experienced WPV in the previous 12 months, and 46% (n = 920) reported WPV only in the previous week. The most significant protective factors were nurses' age, patients' use of illegal substances, attitude of individual nurses and considering effective the organization's procedures for preventing and managing episodes of violence. The most significant risk factors included workload, recognizing violence as an inevitable part of the job, patients' cultural aspects and patients' agitated behaviour. The frequency of WPV was significantly higher in certain areas, such as the emergency department and in mental health wards. Conclusion Workplace violence (WPV) against nurses is a very frequent and concerning issue, especially in hospitals and community services. Based on our findings, integrated and multimodal programmes for prevention and management of WPV are recommended. More attention and resources need to be allocated to reduce WPV by improving the quality of nurses' workplace environment and implementing violence‐free policies for hospitals. Implications for the Profession and/or Patient Care Impact Workplace verbal and physical violence is a widespread phenomenon, both in hospital and community settings, and even during COVID‐19 pandemic. This problem is exacerbated by the lack of effective reporting systems, fear of retaliation and the tendency to consider violence as an inevitable part of the job. The characteristics of professionals, patients, work environment and organizational factors are involved in the spread of workplace violence, determining its multifactorial nature. Integrated and multimodal programmes to prevent and manage of workplace violence are probably the only way to effectively counteract workplace violence against nurses. Healthcare policymakers, managers of hospital and community services need to proactively prevent and effectively manage and monitor episodes of violence. Nurses need to feel protected and safeguarded against any form of verbal or physical violence, to provide high‐quality care in a totally safe environment. Patient or Public Contribution No patient or public contribution.